Pengaruh Perputaran Piutang, Debt To Equity Ratio, Perputaran Persediaan, dan Ukuran Perusahaan Terhadap Profitabilitas - Fransiska, Monas Selviana; Agus Sihono (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2025)
Profitability shows how efficiently a company generates profit by optimizing the use of its owned assets. To management and investors, profitability provides a yardstick to assess how effectively a company uses its assets to achieve profitability. This research aims to investigate the impact of receivable turnover, debt-to-equity ratio, inventory turnover, and firm size on profitability. Employing a purposive sampling approach, the study sampled 9 Indonesian pharmaceutical companies listed on the Indonesia Stock Exchange between 2019 and 2023. Multiple linear regression analysis was employed as a statistical testing tool to analyze secondary data from annual reports. The results show that receivable turnover, inventory turnover, and firm size do not significantly impact profitability, while the debt-to-equity ratio has a significant negative effect.